2022
DOI: 10.3389/fnut.2022.1062961
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin remodels the gut microbiota to ameliorate ulcerative colitis

Abstract: IntroductionUlcerative colitis (UC), a chronic non-specific colorectal inflammatory disease with unclear etiology, has long plagued human health. Gut microbiota dysbiosis destroy homeostasis of the colon, which is closely related to ulcerative colitis progress. Apigenin, a flavonoid widely present in celery, has been found to improve ulcerative colitis. However, the potential molecular mechanism of apigenin ameliorating ulcerative colitis through protecting intestinal barrier and regulating gut microbiota rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…It was reported that [ Eubacterium ]_ fissicatena _ group and Romboutsia were significantly increased in HFD‐fed mice and obese patients, and their high levels were positively correlated with body weight and serum lipids 19,20 . Romboutsia was also increased in esophageal cancer, ulcerative colitis, and diabetic retinopathy, suggesting that Romboutsia may be a potential pathogenic bacterium 21‐23 . Faecalibaculum is a proinflammatory bacterium, which is involved in exacerbating hepatic steatosis and damaging the intestinal barrier 24 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was reported that [ Eubacterium ]_ fissicatena _ group and Romboutsia were significantly increased in HFD‐fed mice and obese patients, and their high levels were positively correlated with body weight and serum lipids 19,20 . Romboutsia was also increased in esophageal cancer, ulcerative colitis, and diabetic retinopathy, suggesting that Romboutsia may be a potential pathogenic bacterium 21‐23 . Faecalibaculum is a proinflammatory bacterium, which is involved in exacerbating hepatic steatosis and damaging the intestinal barrier 24 .…”
Section: Discussionmentioning
confidence: 98%
“…19,20 Romboutsia was also increased in esophageal cancer, ulcerative colitis, and diabetic retinopathy, suggesting that Romboutsia may be a potential pathogenic bacterium. [21][22][23] Faecalibaculum is a proinflammatory bacterium, which is involved in exacerbating hepatic steatosis and damaging the intestinal barrier. 24 Correlation analysis showed that Faecalibaculum was positively correlated with TC and LDL-C. Gemella was significantly increased in obese patients and colon cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…67 Noteworthily, numerous studies have shown that flavonoids can improve intestinal mucosal barrier damage by upregulating the expression of TJs and MUC2 mucin. 68,69 Thus, as a natural flavonoid compound, IQ is expected to protect the integrity of the intestinal mucosal barrier by enhancing the expression of TJs and mucins. In the present study, IQ treatment significantly increased the mRNA expression of ZO-1, Occludin, Claudin-1, and MUC2 in the ileum, revealing that IQ improved intestinal mucosal barrier damage induced by LPS…”
Section: Papermentioning
confidence: 99%
“…34,49,62 It has been reported that DSS treatment increased the relative abundance of Proteobacteria in the intestines of mice. 63,64 The effects of EYPC on the abundance and composition of the gut flora were initially investigated. In contrast to previous studies, after two weeks of dietary EYPC supplementation, no significant difference was found in α-diversity between mice with colitis and those without EYPC supplementation, indicating that the anti-inflammatory effect of EYPC in this study was independent of changes in the diversity of gut microbiota.…”
Section: Papermentioning
confidence: 99%